La música infantil para estimular las emociones en los niños de inicial ii del centro de educación inicial Dr. Pío Jaramillo Alvarado de la ciudad de Loja, periodo 2019 – 2020. - Ruque Quito, Ana Gabriela (2021)
The thesis called: CHILDREN'S MUSIC TO STIMULATE EMOTIONS IN THE CHILDREN OF INICIAL II OF THE CENTRO DE EDUCACIÓN INICIAL DR. PÍO JARAMILLO ALVARADO DE LA CIUDAD DE LOJA, PERIOD 2019-2020, had the general objective of: Improving emotions through children's music in kindergarten II children. The present research had a mixed approach, the methods used were: scientific, inductive, deductive, analytical, synthetic, comparative, descriptive, while the techniques and instruments used were: survey applied to pre-school teachers, and the adapted evaluation form of the test "Multiple Intelligences and the Self-Assessment Questionnaire (CAIM)", which was applied to children of initial II parallel "D". The population consisted of 121 students and 6 teachers, of whom 18 children aged 4 to 5 years and 2 teachers were randomly taken as a sample. This group belonged to the research sample, when evaluated they were found in the following percentages: musical intelligence 61% at the low level, 22% medium and 17% high; intrapersonal intelligence 33% low, 50% medium and 17% high, interpersonal intelligence, 11% low, 72% medium, and high 17% high. In certain cases they are unaware of some emotions and most of them do not know how to locate them correctly, which is why the alternative proposal "Creating Emotions" based on creative and innovative activities was applied to stimulate emotions in children, improving on: musical intelligence 33% medium level and 67% high; intrapersonal intelligence 28% medium level and 72% high; interpersonal intelligence 26% in the medium level and 74% in high, concluding that children's music is an effective methodology for the stimulation of emotions in children, this must be taught from an early age since it allows the child to identify their own feelings and develop empathy with your peers.